2009
DOI: 10.3858/emm.2009.41.5.033
|View full text |Cite
|
Sign up to set email alerts
|

Repression of TNF-α-induced IL-8 expression by the glucocorticoid receptor-β involves inhibition of histone H4 acetylation

Abstract: Increased expression of a number of proinflammatory genes, including IL-8, is associated with inflammatory conditions such as asthma. Glucocorticoid receptor (GR)β, one of the GR isoforms, has been suggested to be upregulated in asthma associated with glucocorticoid insensitivity and to work as a dominant negative inhibitor of wild type GRα. However, recent data suggest that GRβ is not a dominant negative inhibitor of GRα in the transrepressive process and has its own functional role. We investigated the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…2 In addition, poorly defined mechanisms, possibly involving microenvironmental cues, activate alternative splicing of exon 9, which generates mRNA encoding the dominant-negative GR␤ isoform. 2,4 The A3669G (rs6198) SNP in the untranslated region of GR␤ exon 9 stabilizes GR␤ mRNA 5 and is present with an allele frequency between 4% (Sub-Saharan Africans) and 20% (Europeans) in the normal population 6 but at greater frequencies in patients with autoimmune disorders (27% in systemic lupus erythematosus and 42% in rheumatoid arthritis) 5 and in individuals predisposed to central adiposity (30.4%). 7 In this issue of Blood, we describe that the frequency of the A3669G SNP is increased in polycythemia vera (PV; 55%) and that erythroblasts expanded in vitro from these patients express GR␤ and do not respond to corticosteroids.…”
Section: Increased Frequency Of the Glucocorticoid Receptor A3669g (Rmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In addition, poorly defined mechanisms, possibly involving microenvironmental cues, activate alternative splicing of exon 9, which generates mRNA encoding the dominant-negative GR␤ isoform. 2,4 The A3669G (rs6198) SNP in the untranslated region of GR␤ exon 9 stabilizes GR␤ mRNA 5 and is present with an allele frequency between 4% (Sub-Saharan Africans) and 20% (Europeans) in the normal population 6 but at greater frequencies in patients with autoimmune disorders (27% in systemic lupus erythematosus and 42% in rheumatoid arthritis) 5 and in individuals predisposed to central adiposity (30.4%). 7 In this issue of Blood, we describe that the frequency of the A3669G SNP is increased in polycythemia vera (PV; 55%) and that erythroblasts expanded in vitro from these patients express GR␤ and do not respond to corticosteroids.…”
Section: Increased Frequency Of the Glucocorticoid Receptor A3669g (Rmentioning
confidence: 99%
“…2,3 V2R inhibition attenuates progression of CKD in rodent orthologs of ADPKD. 4 Tolvaptan, a V2R antagonist, is effective treatment for hyponatremia and is being evaluated in clinical trials as treatment for ADPKD. 4,5 Tolvaptan's effects on dDAVP stimulation of VWF have not been reported.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…With the formation of new blood vessels and the vertical growth of tumors, an influx of immune cells occurs as a result of shed molecules like IL-8 (Waugh & Wilson, 2008). As previously discussed, IL-8 as well as IL-6 can act as circulating tumor cell attractants, which can accelerate tumor growth, angiogenesis, and recruitment of other chemoattractants (Kim et al, 2009). IL-8 signaling has also been shown to increase the transcription of nuclear factor-κB in melanoma, which may be increased through protein kinase C (PKC) activity (Wang & Richmond, 2001).…”
Section: Angiogenesismentioning
confidence: 97%
“…13,[16][17][18] Indeed, hGRβ does not bind natural or synthetic glucocorticoids; it resides in the nucleus of certain cell types, such as epithelial cells and neutrophils and exerts inhibitory effects on the transcriptional activity of the hGRα through well-studied molecular mechanisms. [19][20][21] However, given that studies from several groups have demonstrated that hGRβ can directly induce or repress a number of target genes, [22][23][24][25] while Chatzopoulou and collaborators recently revealed that GRβ does not have transcriptional activity in zebrafish, 26 it is evident that the specific functional role of GRβ remains to be elucidated. New evidence suggests that hGRβ has an important role in insulin signaling and might be involved in gluconeogenesis and inflammation in mouse liver.…”
Section: Glucocorticoid Receptor: From the Nr3c1 Gene To Protein Isofmentioning
confidence: 99%